2017
DOI: 10.1037/pag0000179
|View full text |Cite
|
Sign up to set email alerts
|

Feeling sad makes us feel older: Effects of a sad-mood induction on subjective age.

Abstract: A mood-induction paradigm was implemented in a sample of 144 adults covering midlife and old age (40-80 years) to investigate associations between mood and subjective age. Sad or neutral mood was induced by texts and music pieces. Subjective age was operationalized as felt age relative to chronological age. Participants receiving the sad-mood induction reported changes toward older felt ages from pre- to postinduction. Participants receiving the neutral-mood induction reported comparable levels of subjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…Armenta et al (2018) extended these ଏndings to the workplace and showed that age-related work events (i.e., age declines or age discrimination) drive daily relative subjective age perceptions. Furthermore, recent studies suggest that even general mood inductions can aଏect (relative) subjective age perceptions (Dutt & Wahl, 2017). The authors argued that negative events can cause negative mood, which functions as a heuristic for evaluation judgements (see Dutt & Wahl, 2017; also see Schwarz & Clore, 1983 and, thus, aଏect (relative) subjective age perceptions (Dutt & Wahl, 2017).…”
Section: Role Of Negative Work Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…Armenta et al (2018) extended these ଏndings to the workplace and showed that age-related work events (i.e., age declines or age discrimination) drive daily relative subjective age perceptions. Furthermore, recent studies suggest that even general mood inductions can aଏect (relative) subjective age perceptions (Dutt & Wahl, 2017). The authors argued that negative events can cause negative mood, which functions as a heuristic for evaluation judgements (see Dutt & Wahl, 2017; also see Schwarz & Clore, 1983 and, thus, aଏect (relative) subjective age perceptions (Dutt & Wahl, 2017).…”
Section: Role Of Negative Work Eventsmentioning
confidence: 99%
“…The authors argued that negative events can cause negative mood, which functions as a heuristic for evaluation judgements (see Dutt & Wahl, 2017; also see Schwarz & Clore, 1983 and, thus, aଏect (relative) subjective age perceptions (Dutt & Wahl, 2017). Translated to the work context, we assume that negative work events induce negative mood and thus increase employees' (relative) subjective age perception (see Dutt & Wahl, 2017), which is potentially also mediated through a diଏerent OFTP (Zacher & Frese, 2009) of employees perceiving more or less negative events. In particular, we investigate general negative events at work, e.g., interpersonal conଏicts, negative feedback and discrimination (see Appendix A) as drivers of (relative) subjective age variability.…”
Section: Role Of Negative Work Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research also shows that objective physical/functional health conditions and self-perceptions of health explain the largest proportions of variance in felt age, with poorer health contributing to feeling older (Ambrosi-Randić et al, 2018; Barrett, 2003; Bergland et al, 2014; Demakakos et al, 2007; Hubley & Russell, 2009). Felt age is also associated with psychological health factors such as self-efficacy, internal locus of control, optimism, extraversion, and openness (Bellingtier & Neupert, 2020; Canada et al, 2013; Hubley & Hultsch, 1994; Teuscher, 2009); depressive symptoms (Choi & DiNitto, 2014); positive/negative affect and life satisfaction (Dutt & Wahl, 2017; Kotter-Grühn et al, 2015); and memory self-efficacy and cognitive test scores (e.g., word-list memory recall; Ihira et al, 2015; Stephan et al, 2011).…”
mentioning
confidence: 99%